Eldonioids with associated trace fossils from the lower Cambrian Emu Bay Shale Konservat-Lagerstätte of South Australia. (19th January 2018) - Schroeder, Natalie I.; Paterson, John R.; Brock, Glenn A.
Abstract: Rare specimens of eldonioids recovered from the lower Cambrian (Series 2, Stage 4) Emu Bay Shale (EBS) Konservat-Lagerstätte represent the first record of the group for the Cambrian of East Gondwana. The disc-shaped body of the EBS taxon bears fine concentric corrugations on the dorsal surface and, ventrally, a series of internal lobes that have primary and secondary bifurcations, as well as a coiled sac. It appears to be most similar to Rotadiscus and Pararotadiscus of the Cambrian Chengjiang and Kaili biotas of South China, respectively. While the structure of the internal lobes would indicate that this occurrence in the EBS represents a new taxon within the Rotadiscidae, lack of detail regarding the precise number of internal lobes and the condition of the circumoral tentacles warrants a more conservative approach in leaving the genus and species under open nomenclature. The EBS specimens also host trace fossils, including the remains of a burrow, which are generally lacking in the body-fossil-bearing layers of the Konservat-Lagerstätte interval. These traces appear to have been made by small organisms and are similar to traces associated with the discs of Pararotadiscus guizhouensis (Zhao and Zhu, 1994 ) from the Kaili Biota. The available taphonomic, paleoenvironmental, and ichnological evidence indicates that the EBS eldonioids are most likely vagrants that were transported or settled into the 'preservational trap' and subsequently exposed on the substrate for a brief period before burial, thereby allowing organisms to exploit their carcasses for nutrients or other purposes.